Forest Biomass - From Trees to Energy 2021
DOI: 10.5772/intechopen.95417
|View full text |Cite
|
Sign up to set email alerts
|

Evergreen Oak Biomass Residues for Firewood

Abstract: This chapter presents the assessment of the availability for residential heating of residual biomass from cork and holm oaks in a 12,188 ha agroforest area in Portugal. First, the above-ground biomass of evergreen oaks using very high spatial resolution satellite images was determined, followed by the definition of different scenarios for residues removal from the stands. The useful energy potential of the firewood that can be collected from the study area under the various silviculture scenarios was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The LCA of Austrian and Slovenian raw wood production was recently published [14]. Firewood is still commonly used as a primary energy source worldwide [15][16][17]. Through a critical review of the literature and available secondary sources, no LCA studies and research available for wood-based heating systems in Slovenia could be found.…”
Section: Biomass As Energy Source For Residential Heating Systemsmentioning
confidence: 99%
“…The LCA of Austrian and Slovenian raw wood production was recently published [14]. Firewood is still commonly used as a primary energy source worldwide [15][16][17]. Through a critical review of the literature and available secondary sources, no LCA studies and research available for wood-based heating systems in Slovenia could be found.…”
Section: Biomass As Energy Source For Residential Heating Systemsmentioning
confidence: 99%
“…The residues obtained from forest management practices in Portugal are already valorized to some extent. In 2019, most (53%) of the energy from firewood, forest and plant residues, pellets, and other agglomerates was consumed in the residential sector [10], which mainly uses biomass for heating [11]. The choice for the source of wood in households is much dependent on the composition of the local forest, and the Eucalyptus globulus is important in the regions were the species is abundant.…”
Section: Introductionmentioning
confidence: 99%